Evaluating K-means multidimensional big data clusters through MapReduce paradigm - ., Agnivesh; Pandey, Rajiv; Singh, Amarjeet (International Journal of Engineering and Technology, 2026)
In the era of big data, with the increasing use of large-scale data-driven applications, clustering and extracting useful information from big datasets has posed challenges. Prevailing clustering algorithms need globally optimized solutions for big datasets. K-means algorithm for clustering is of great interest because of its simplicity. However, there are certain limitations in K-means for analyzing big data which leave scope for successive improvements. This research work presents a new K-means clustering algorithm by improving K-means in MapReduce paradigm. The proposed work presents a method to find initial seeds of clusters instead of randomly selecting them which is a major drawback in standard K-means for clustering big data. The research minimizes MapReduce iteration dependence also. Moreover, the presented algorithm takes into consideration between cluster separation and within cluster compactness to achieve high performance. To obtain efficiency, cloud computing is applied in which Amazon Elastic MapReduce 5.x is used. It distributes the job of clustering among various nodes in parallel using low cost machines. The proposed work is simulated on some real datasets from UC Irvine Machine Learning Repository. The results confirm that the research work models an effective algorithm for clustering Big Data.